Is mother's financial autonomy associated with stunting among children aged 7-35 months: An empirical study from India. - Shirisha P; Anjali Bansal (Public Library of Science (PLoS), 2022)
Stunting depicts chronic deprivation and is a huge public health problem in several developing countries. Considering the sociocultural and sociodemographic factors of India, we aimed to examine the relationship between maternal autonomy and stunting among children <35 months. We have used the data from the latest round of National Family health survey conducted in 2015-16. The main exposure variable was women's autonomy which are represented in our study by the four dimensions- decision-making, physical mobility, financial autonomy, attitudes towards domestic violence, the main predictor variable was stunting among children. Chi-square analysis, univariate and multivariable binary logistic regression analysis were performed to find the association of childhood stunting and women's autonomy. The results were reported at 5% level of significance. All the autonomy variables have shown a significant association with child stunting at 5% level of significance. The unadjusted odds of stunting were found to be significant with respect to all the four dimensions of autonomy variables except physical autonomy. However, after adjusting for other explanatory factors attenuated these relationships and made them statistically insignificant except for women's economic autonomy (AOR = 0.91; 95% C.I.-(0.85, 0.98)) which was found to be significantly affecting the child's status of stunting. Our study reinforces that maternal autonomy is a significant predictor of childhood stunting. Hence, we recommend that policy makers, while designing interventions and policies, must address the socioeconomic inequalities at the community level while devising ways to improve women's empowerment. As it has far-reaching consequences on the nutrition status of the upcoming generations.